2018
DOI: 10.1016/j.ijid.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multidrug resistant organisms on the outcome of diabetic foot infection

Abstract: Among rehospitalized patients, methicillin resistant Staphylococcus infections was detected as the most common agent, and Klebsiella spp. infections were found to be significantly associated with fatality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 33 publications
2
56
1
12
Order By: Relevance
“…In accordance to our study, Konar & Das, Saseedharan et al and Saltoglu et al reported 36.84%, 23.7% & 31% MRSA isolates, respectively [10,11,19]. However, Bansal et al and Otta et al observed 55.56% and 77.8 %MRSA isolates in their study which is high in comparison to our study [6,9].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In accordance to our study, Konar & Das, Saseedharan et al and Saltoglu et al reported 36.84%, 23.7% & 31% MRSA isolates, respectively [10,11,19]. However, Bansal et al and Otta et al observed 55.56% and 77.8 %MRSA isolates in their study which is high in comparison to our study [6,9].…”
Section: Discussionsupporting
confidence: 88%
“…They observed Pseudomonas aeruginosa (21.67%) to be predominant followed by Staphylococcus aureus (18.88%), Escherichia coli (18.18%) and Klebsiella pneumoniae (16.78%). [6] However, Otta et al and Saltoglu et al reported Staphylococcus aureus (30%, 20%) to be the predominant isolate followed by Pseudomonas aeruginosa (11.7%, 19%) and Escherichia coli (10%, 12%) [9,19] In contrast, Konar and Das reported Pseudomonas aeruginosa (31.34%) as the most commonly isolated organism followed by Escherichia coli (23.8%) and Staphylococcus aureus (22.4%) [10]. This is similar to the findings by Shanmugam et al who reported Pseudomonas spp (16%) followed by Escherichia coli (14.6%) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common bacterial isolates from diabetic ulcers in this study were Staphylococci species 40.8% compatible to other findings showed that Staphylococci species accounted 43.37%[23], whereas Gram negative bacteria were the most frequently pathogenic agents reported in other studies 51%[24], 56.1%[25], 61%[26], 67%[27] and 51.2%[28].Interestingly, our study revealed high rate of S. aureus 14.3%, S. epidermidis 14.3%, S. saprophyticus 9.5% and MRSA 4.8%. These results were compatible with the findings of other studies showed that S. aureus 19.4%, S. epidermidis 18.4% and other Staphylococci species 3.6%[29], Other study showed the most commonly isolated S. aureus 30%, followed by S. saprophyticus 19% and S. epidermidis 10%[30].…”
supporting
confidence: 91%
“…Although age-related immunosenescence may be associated with infection-related mortality, it is also associated with diseases such as diabetes mellitus and chronic kidney disease (22,23). Moreover, there may be a difference between biological age and chronological age.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 99%